Characterization of pea (Pisum sativum) seed protein fractions. (8th July 2013) - Rubio, Luis A; Pérez, Alicia; Ruiz, Raquel; Guzmán, M Ángeles; Aranda‐Olmedo, Isabel; Clemente, Alfonso
Abstract BACKGROUND Legume seed proteins have to be chemically characterized in order to properly link their nutritional effects with their chemical structure. RESULTS Vicilin and albumin fractions devoid of cross‐contamination, as assessed by mass peptide fingerprinting analysis, were obtained from defatted pea (Pisum sativum cv. Bilbo) meal. The extracted protein fractions contained 56.7–67.7 g non‐starch polysaccharides kg−1. The vicilin fraction was higher than legumins in arginine, isoleucine, leucine, phenylalanine and lysine. The most abundant amino acids in the albumin fraction were aspartic acid, glutamic acid, lysine and arginine, and the amounts of methionine were more than double than those in legumins and vicilins. The pea albumin fraction showed a clear enrichment of protease inhibitory activity when compared with the seed meal. In vitro digestibility values for pea proteins were 0.63 ± 0.04, 0.88 ± 0.04 and 0.41 ± 0.23 for legumins, vicilins and albumins respectively. CONCLUSION Vicilin and albumin fractions devoid of cross‐contamination with other proteins were obtained from pea seed meal. The vicilin fraction also contained low amounts of soluble non‐starch polysaccharides and was enriched in isoleucine, leucine, phenylalanine and lysine. In vitro digestibility values for pea proteins were similar or even numerically higher than those for control proteins. © 2013 Society of Chemical Industry